Functionalized bone repair hydrogel scaffold, preparation method and application
The porous hydrogel scaffold formed by the composite of nano-concave-concave-rodite and methacrylylated gelatin loads mesenchymal stem cell exosomes and miRNA, solving the limitations of existing bone defect repair materials, achieving stable release and immune regulation, and significantly improving bone repair efficiency.
Patent Information
- Application Number
- CN202510735036.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-04
- Publication Date
- 2025-08-22
AI Technical Summary
The existing bone defect repair materials have problems such as limited supply source, immune rejection, insufficient osteogenesis induction performance and surgical complications. The direct application of mesenchymal stem cell exosomes has instability in release and low targeted delivery efficiency, making it difficult to fully exert the efficacy.
Nanoconcave and methacrylylated gelatin are combined to form a porous three-dimensional hydrogel scaffold, which is loaded with mesenchymal stem cell exosomes and specific microRNAs. Through the highly adsorption and slow release mechanism, the local immune microenvironment is regulated and bone regeneration is promoted.
It realizes stable load and controlled release of MSC-Exos, significantly accelerates bone defect repair, improves the repair efficiency of large-volume bone defects, has good biocompatibility and mechanical support performance, and is suitable for large-segment bone defect repair and tissue engineering.
Smart Images

Figure CN120514929A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biomedical materials, and in particular relates to a hydrogel scaffold loaded with mesenchymal stem cell exosomes for promoting bone defect repair, a preparation method and applications thereof. Background Art
[0002] Bone defects are a common and challenging clinical problem in orthopedics, especially large bone defects caused by severe trauma, tumor resection, infection, or congenital developmental abnormalities, which often exceed the body's self-repair capacity and are difficult to heal. Current clinical approaches to bone repair mainly use autologous bone transplantation and allogeneic bone transplantation, but these methods are limited by limited supply, immune rejection, insufficient osteoinduction, and surgical complications. Therefore, the development of new and efficient bone tissue repair materials to promote bone regeneration has become an urgent issue in this field.
[0003] Studies in recent years have shown that the body's immune microenvironment plays an important regulatory role in the regeneration process during bone defect repair. Among them, macrophages play a key role in different stages of bone repair, especially M2 macrophages that tend to be anti-inflammatory phenotypes, which can promote osteoblast differentiation and bone tissue regeneration by secreting growth factors and anti-inflammatory cytokines. In addition, the efferocytosis function of macrophages (the ability to clear apoptotic cells) is important for timely removal of cell debris at the site of injury, inhibiting persistent inflammatory responses, and promoting tissue repair. If the efferocytosis function of macrophages is impaired, apoptotic cells that are not cleared in time will release inflammatory mediators, resulting in long-term local inflammation and hindering new bone formation.
[0004] Mesenchymal stem cell exosomes (MSC-Exos), as an emerging cell-free biotherapeutic strategy, have shown great potential in the field of bone tissue engineering. Studies have shown that MSC-Exos can regulate the function of immune cells (such as promoting the transformation of macrophages to the M2 phenotype) and directly or indirectly promote osteogenic differentiation, thereby contributing to the repair of bone defects. However, when MSC-Exos are directly applied to bone defects, there are problems such as unstable release and low efficiency of targeted delivery, which makes it difficult to fully exert its therapeutic effect. Therefore, there is an urgent need for a new scaffold material that can stably load and control the release of MSC-Exos, which not only provides the necessary support and osteogenic microenvironment, but also can effectively regulate the local immune status to accelerate bone tissue regeneration. Summary of the Invention
[0005] The purpose of the present invention is to address the problems existing in the above-mentioned prior art and provide a functional bone repair hydrogel scaffold, preparation method and application. The scaffold can load mesenchymal stem cell exosomes and specific microRNA (miRNA) to regulate the immune microenvironment of the damaged area and promote bone regeneration, thereby effectively improving the repair effect of large-volume bone defects.
[0006] In order to achieve the above objectives, the technical solution provided by the present invention is:
[0007] On the one hand, the technical solution provided by the present invention is:
[0008] A method for preparing a functionalized bone repair hydrogel scaffold comprises the following steps:
[0009] Nano-attapulgite is mixed with methacrylated gelatin to form a printable emulsion system, the printable emulsion system is three-dimensionally printed and ultraviolet cross-linked to form a porous three-dimensional scaffold, and the porous three-dimensional scaffold is incubated in a PBS solution containing mesenchymal stem cell exosomes and miRNA-26a-5p and / or miRNA-30a-5p, so that the mesenchymal stem cell exosomes and miRNA-26a-5p and / or miRNA-30a-5p are co-loaded on the porous three-dimensional scaffold.
[0010] The present invention provides a mesenchymal stem cell exosome hydrogel bone repair scaffold loaded with miRNAs. The hydrogel scaffold is composed of nano-attapulgite (ATP) and methacrylated gelatin (GelMA) to form a porous three-dimensional network structure. The high adsorption property of ATP is used to enrich MSC-Exos, wherein the exosomes are loaded with the reverse sequence of miRNA-26a-5p and / or miRNA-30a-5p (i.e., inhibitors of miRNA-26a-5p and miRNA-30a-5p). Due to the high adsorption properties of nano-attapulgite, the exosomes and the above-mentioned miRNAs can be effectively adsorbed and evenly distributed inside the scaffold. After the scaffold is implanted in the bone defect site, it can slowly release the loaded exosomes and miRNAs, allowing them to continuously exert their biological effects.
[0011] In some preferred embodiments, the step of mixing to form a printable emulsion system specifically includes:
[0012] Nano-attapulgite powder is mixed with a methacrylated gelatin solution, and a photoinitiator, lithium phenol-2,4,6-trimethylphenylphosphonate, and a cross-linking agent, triethanolamine, are added to the resulting mixture, and the mixture is magnetically stirred to obtain a uniform aqueous phase. The aqueous phase is magnetically stirred and uniformly mixed with an oil phase mixed with dodecane and octane, and then ultrasonically treated to obtain a stable, uniform, and printable Pickering emulsion, wherein the mass ratio of nano-attapulgite powder to methacrylated gelatin, lithium phenol-2,4,6-trimethylphenylphosphonate, and triethanolamine is (1.0-4.0):(5.0-15.0):(0.05-0.3):(0.05-0.3), and the volume ratio of the aqueous phase to the oil phase is 1:1-1:6.
[0013] In some preferred embodiments, the printing cross-linking step specifically includes:
[0014] The nozzle temperature is set to 20-30° C., the extrusion pressure is set to 0.1-0.3 MPa, and the printing speed is set to 1-5 mm / s. Three-dimensional printing is performed according to the printing parameters. After printing is completed, cross-linking is performed under 365-405 nm ultraviolet light for 5-15 minutes.
[0015] In some preferred embodiments, the incubation step specifically includes:
[0016] The porous three-dimensional scaffold was immersed in a PBS solution containing 0.5–2 μg / mL MSC-Exos, 200–500 nM miRNA-26a-5p, and 200–500 nM miRNA-30a-5p, and incubated at 25–45°C for 4–24 h to complete the loading.
[0017] In some preferred embodiments, wherein the miRNA is miRNA-26a-5p, miRNA-30a-5p or a combination thereof, when a single miRNA is loaded, the molar ratio of the mesenchymal stem cell exosomes to the loaded miRNA is 1:50 to 1:500; when a combination of miRNAs is loaded, the molar ratio of the mesenchymal stem cell exosomes to the loaded miRNA is
[0018] 1:50~1:500; the molar ratio of mesenchymal stem cell exosomes to loaded miRNA-30a-5p is 1:50~1:500; the molar ratio of miRNA-26a-5p to miRNA-30a-5p is 1:0.5~1:2. 6. The preparation method of a functionalized bone repair hydrogel scaffold according to claim 1 is characterized in that the mesenchymal stem cell exosomes are extracted by ultracentrifugation and have an average particle size of 100–140 nm.
[0019] In some preferred embodiments, the porous three-dimensional scaffold has a pore size of 60-150 μm and a compressive strength of 1000-3000 kPa.
[0020] On the other hand, the technical solution provided by the present invention is:
[0021] A functionalized bone repair hydrogel scaffold is prepared by the above method. The functionalized bone repair hydrogel scaffold has a three-dimensional porous structure and its surface is stably loaded with components such as mesenchymal stem cell exosomes and the miRNA-26a-5p and / or miRNA-30a-5p they carry.
[0022] On the other hand, the technical solution provided by the present invention is:
[0023] A use of the above bone repair hydrogel scaffold in bone defect repair.
[0024] On the other hand, the technical solution provided by the present invention is:
[0025] A use of the above-mentioned bone repair hydrogel scaffold in a tissue engineering material for regulating the SOCS3 signaling pathway and reducing the expression of inflammatory factors.
[0026] Beneficial effects:
[0027] The preparation method provided by the present invention has low cost, simple process steps and mild reaction conditions, good loading effect, and RNA The good printing effect provides reliable guarantee for subsequent applications, ensuring that more than 90% miRNA activity is retained, with good in vivo efficacy, high production efficiency and excellent product performance, making it suitable for promotion.
[0028] The present invention provides a mesenchymal stem cell exosome hydrogel bone repair scaffold loaded with miRNAs. The hydrogel scaffold is composed of nano-attapulgite (ATP) and methacryloylated gelatin (GelMA) to form a porous three-dimensional network structure, and the high adsorption of ATP is used to enrich mesenchymal stem cell exosomes (MSC-Exos). MSC-Exos are nanoscale vesicles secreted by mesenchymal stem cells, which can carry a variety of bioactive components such as miRNA and mRNA to mediate intercellular communication. The reverse sequence of miRNA-26a-5p and / or miRNA-30a-5p (i.e., inhibitors of miRNA-26a-5p and miRNA-30a-5p) is loaded in the mesenchymal stem cell exosomes. The present invention uses nano-attapulgite as an RNA carrier and utilizes its high specific surface area and strong adsorption properties to enable exosomes and miRNAs to be efficiently captured and evenly distributed inside the three-dimensional scaffold, ensuring the stable loading and spatially controllable distribution of RNA molecules. At the same time, with the help of the multi-point adsorption effect of ATP, RNA can be released in different time periods and at different peaks, so that different targets can be regulated in a timely manner, avoiding receptor competition or nuclease degradation, and significantly enhancing the stability and functional durability of RNA. After the scaffold is implanted in the bone defect site, it can slowly release the loaded exosomes and miRNAs, allowing them to continue to exert their biological effects. The scaffold uses the high adsorption capacity of ATP to stably load MSC-Exos, achieving slow and sustained release of miRNA, which can effectively regulate the efferocytosis function and immune microenvironment of macrophages, thereby inhibiting the inflammatory response, promoting osteogenic differentiation, and significantly accelerating the repair process of bone defects.
[0029] The present invention focuses on the polarization of macrophages M1 to M2 at the bone defect site. The miRNA-26a-5p slowly released with the scaffold can target and inhibit the expression of ADAM17, protect the function of the MerTK receptor on the surface of macrophages, thereby enhancing the phagocytic clearance of apoptotic cells by macrophages (endocytosis), and accelerate the resolution of inflammation at the injury site; while the slowly released miRNA-30a-5p reverse sequence can upregulate the expression of SOCS3 in macrophages, inhibit the excessive activation of the NF-κB signaling pathway, reduce the production of inflammatory factors, and induce macrophages to transform from the pro-inflammatory M1 type to the anti-inflammatory M2 type. These two nucleic acid molecules improve the tissue repair function of macrophages through different pathways. The bioactive factors slowly released by the scaffold can also promote the migration, adhesion and osteogenic differentiation of bone marrow mesenchymal stem cells (BMSC), providing support for new bone formation. The composite hydrogel scaffold provided by the present invention has good biocompatibility and mechanical support properties, has broad clinical application prospects, and is suitable for the fields of large bone defect repair, radiation bone injury treatment, and tissue engineering. When the two miRNAs are used simultaneously, they also have the dual functions of immune regulation and osteogenesis induction. Through pathway complementarity, the dual-target combination synergistically enhances macrophage M2 polarization and significantly improves the repair efficiency of large bone defects. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the construction of the exosome hydrogel scaffold loaded with miRNAs of the present invention and its mechanism of regulating the immune microenvironment to promote osteogenesis.
[0031] Figure 2 This is a characterization diagram of the exosomes extracted by the present invention. Figure 2 (A) Western blot analysis of exosome markers Alix and TSG101; Figure 2 (B) The particle size distribution and concentration of stem cell exosomes (MSC-Exos) observed by nanoparticle tracking analysis (NTA); Figure 2 (C) is an image of tdtomato-labeled exosomes; Figure (D) is an image of exosome morphology observed by transmission electron microscopy (TEM).
[0032] Figure 3 This is a characterization diagram of the miRNA-loaded exosomes of the present invention. Figure 3 (A) shows the size distribution and concentration of exosomes loaded with miRNA-26a-5p; Figure 3 (B) is the morphology of mesenchymal stem cell exosomes loaded with miRNA-26a-5p; Figure 3 (C) shows the particle size distribution and concentration of exosomes loaded with miRNA-30-5p inhibitors; Figure 3 (D) Morphological image of exosomes loaded with miRNA-30-5p inhibitor.
[0033] Figure 4 The scanning electron microscope (SEM) image of the miRNA-loaded exosome hydrogel scaffold constructed in the embodiment of the present invention and the fluorescence image of the scaffold rich in exosomes are shown. Figure 4 (A) Scanning electron microscopy (SEM) image of MSC-Exos scaffold; Figure 4 (B) Fluorescence image of exosome-enriched scaffold; Figure 4 (C) Compressive strength diagram.
[0034] Figure 5 Graph showing the release characteristics of exosomes from the scaffold of the present invention. Figure 5 (A) shows the release of exosomes from the scaffold; Figure 5 (B) is a graph showing the cumulative release rate of exosomes.
[0035] Figure 6 This is an H&E staining analysis of the early inflammatory response after the hydrogel scaffold of the present invention was implanted into the rat skull defect.
[0036] Figure 7This is an H&E staining analysis of the promotion of new bone formation after the hydrogel scaffold of the present invention was implanted into the rat skull defect. DETAILED DESCRIPTION
[0037] A method for preparing a functionalized bone repair hydrogel scaffold comprises the following steps:
[0038] Nano-attapulgite is mixed with methacrylated gelatin to form a printable emulsion system, the printable emulsion system is three-dimensionally printed and ultraviolet cross-linked to form a porous three-dimensional scaffold, and the porous three-dimensional scaffold is incubated in a PBS solution containing mesenchymal stem cell exosomes and miRNA-26a-5p and / or miRNA-30a-5p, so that the mesenchymal stem cell exosomes and miRNA-26a-5p and / or miRNA-30a-5p are co-loaded on the porous three-dimensional scaffold.
[0039] Preferably, the step of mixing to form a printable emulsion system specifically includes:
[0040] Nano-attapulgite powder is mixed with a methacrylated gelatin solution, and a photoinitiator, lithium phenol-2,4,6-trimethylphenylphosphonate, and a cross-linking agent, triethanolamine, are added to the resulting mixture, and the mixture is magnetically stirred to obtain a uniform aqueous phase. The aqueous phase is magnetically stirred and uniformly mixed with an oil phase mixed with dodecane and octane, and then ultrasonically treated to obtain a stable, uniform, and printable Pickering emulsion, wherein the mass ratio of nano-attapulgite powder to methacrylated gelatin, lithium phenol-2,4,6-trimethylphenylphosphonate, and triethanolamine is (1.0-4.0):(5.0-15.0):(0.05-0.3):(0.05-0.3), and the volume ratio of the aqueous phase to the oil phase is 1:1-1:6.
[0041] Preferably, the printing cross-linking step specifically includes:
[0042] The nozzle temperature is set to 20-30° C., the extrusion pressure is set to 0.1-0.3 MPa, and the printing speed is set to 1-5 mm / s. Three-dimensional printing is performed according to the printing parameters. After printing is completed, cross-linking is performed under 365-405 nm ultraviolet light for 5-15 minutes.
[0043] Specifically, the incubation step includes:
[0044] The porous three-dimensional scaffold was immersed in a PBS solution containing 0.5–2 μg / mL MSC-Exos, 200–500 nM miRNA-26a-5p, and 200–500 nM miRNA-30a-5p, and incubated at 25–45°C for 4–24 h to complete the loading.
[0045] Furthermore, the miRNA is miRNA-26a-5p, miRNA-30a-5p or a combination thereof, and when a single miRNA is loaded, the molar ratio of mesenchymal stem cell exosomes to the loaded miRNA is 1:50 to 1:500; when a combination of miRNAs is loaded, the molar ratio of mesenchymal stem cell exosomes to the loaded miRNA-26a-5p is 1:50 to 1:500; the molar ratio of mesenchymal stem cell exosomes to the loaded miRNA-30a-5p is 1:50 to 1:500; the molar ratio of miRNA-26a-5p to miRNA-30a-5p is 1:0.5 to 1:2. 6. The method for preparing a functional bone repair hydrogel scaffold according to claim 1 is characterized in that the mesenchymal stem cell exosomes are extracted by ultracentrifugation and have an average particle size of 100–140 nm.
[0046] Specifically, the porous three-dimensional scaffold has a pore size of 60-150 μm and a compressive strength of 1000-3000 kPa.
[0047] High concentrations of mesenchymal stem cell exosomes and miRNA can easily lead to increased viscosity and pore blockage. This application achieves uniform dispersion by adjusting the concentration of nano-attapulgite and methacrylated gelatin and optimizing printing pressure and speed. The shear rate is also optimized. SEM and porosity tests confirm that the porosity remains at 65–70% at maximum load, without pore blockage.
[0048] A functionalized bone repair hydrogel scaffold is prepared by the above method. The functionalized bone repair hydrogel scaffold has a three-dimensional porous structure and its surface is stably loaded with components such as mesenchymal stem cell exosomes and the miRNA-26a-5p and / or miRNA-30a-5p they carry.
[0049] A use of the above bone repair hydrogel scaffold in bone defect repair.
[0050] A use of the above-mentioned bone repair hydrogel scaffold in a tissue engineering material for regulating the SOCS3 signaling pathway and reducing the expression of inflammatory factors.
[0051] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.
[0052] All raw materials of the present invention are not particularly limited in their sources and can be purchased from the market or prepared according to conventional methods well known to those skilled in the art.
[0053] All raw materials of the present invention are not particularly limited in purity. The present invention preferably uses analytically pure or prepared
[0054] All raw materials and process steps of the present invention, and their brands or abbreviations are conventional brands or abbreviations in the art. Each brand or abbreviation is clear and unambiguous within the field of its relevant use. Those skilled in the art can purchase them commercially or prepare them by conventional methods, or implement them using corresponding equipment, based on the brand, abbreviation and corresponding use.
[0055] Example 1: Construction of MSC-Exos hydrogel scaffold loaded with miRNA-26a-5p on ATP (2%) / GelMA (10%) scaffold and analysis of its biological function
[0056] 1. Construction of MSC-Exos Hydrogel Scaffolds Loaded with miRNA-26a-5p
[0057] 2% nano-attapulgite (ATP) powder was mixed with a 10% methacrylated gelatin (GelMA) solution. To the resulting mixture, 0.3 wt% lithium phenol-2,4,6-trimethylphenylphosphonate (LAP) photoinitiator and 0.1 wt% triethanolamine (TEA) crosslinking agent were added, and the mixture was magnetically stirred at room temperature for 5 minutes. The aqueous phase was then mixed with a 30 vol% dodecane / octane oil phase (1:1 mass ratio) at a volume ratio of 30:70 at 1000 rpm for 3 minutes, followed by ultrasonic treatment (150 W) for 5 minutes to obtain a uniform and stable Pickering emulsion. The Pickering emulsion was then printed into porous cylindrical scaffolds with a diameter of 6 mm and a height of 1 mm at a nozzle temperature of 25°C, an extrusion pressure of 0.2 MPa, and a printing speed of 3 mm / s. After printing, the scaffolds were cross-linked by irradiation with 405 nm UV light for 10 minutes, resulting in a porous three-dimensional hydrogel scaffold. The scaffold was immersed in a PBS solution containing 1 μg / mL MSC-Exos and 337 nM miRNA-26a-5p, incubated at 37 °C for 12 h, then removed and gently washed with PBS to obtain the MSC-Exos hydrogel scaffold loaded with miRNA-26a-5p. The detailed preparation process is as follows: Figure 1 shown.
[0058] 2. Extraction and Characterization of MSC-Exos
[0059] Mouse bone marrow mesenchymal stem cells (mBMSCs) were cultured in DMEM / F12 medium supplemented with 10% FBS until 80% confluency, then replaced with Exos-free fetal bovine serum medium and cultured for an additional 48 hours. The supernatant was collected and centrifuged sequentially (300×g, 2000×g, and 10,000×g) to remove debris. Exos were then precipitated by ultracentrifugation at 100,000×g for 2 hours.
[0060] Further characterization of exosomes, such as Figure 2 AD shows:
[0061] -NTA detection particle size is concentrated in 110–140 nm, with a concentration of approximately 2×10 9 / mL;
[0062] -Western blot detection showed positive expression of CD63 and TSG101 proteins, verifying the successful extraction.
[0063] -Fluorescence microscopy images of tdTomato-labeled exosomes
[0064] -TEM shows typical vesicle-like structure;
[0065] 3. Characterization of miRNA-loaded Exosomes
[0066] FITC-labeled miRNA-26a-5p was loaded into MSC-Exos via electroporation. Flow cytometry and fluorescence confocal microscopy showed that the loading efficiency was highly co-localized with CD63, with a loading rate exceeding 90%. Figure 3 As shown in A and B, the particle size of exosomes loaded with miRNA-26a-5p is concentrated in 120–140 nm, and the concentration is about 1.6×10 7 / mL, TEM showed typical vesicle structure.
[0067] 4. Scaffold structure and exosome release performance
[0068] SEM analysis:
[0069] After drying, the scaffolds were metallized. Scanning electron microscopy revealed a uniform porous structure on both the cross-section and surface, with pore sizes ranging from 380–420 μm, which facilitates cell attachment and nutrient exchange. The average compressive strength tested was 1500 kPa.
[0070] Exos load situation:
[0071] After Exos were labeled with FITC and imaged on the scaffold surface, the fluorescence signal was evenly distributed, indicating that the scaffold had high adsorption efficiency and consistent distribution.
[0072] Exos release pattern:
[0073] The cells were cultured in PBS at 37°C, and the supernatant was collected at designated time points. The amount of exosome protein released was measured using a BCA assay. The results showed that exosome release was a slow and continuous process, with approximately 80% of the total amount released within 14 days.
[0074] miRNA release pattern:
[0075] A fluorescent probe complementary to the miRNA-26a-5p sequence was designed and used to detect the released miRNA in the supernatant. The results showed that the miRNA was continuously released from the scaffold for at least 12 days, without a sudden release.
[0076] 5. Animal experiments to evaluate the effects of immune regulation and bone repair
[0077] A SD rat skull defect model was established, and one scaffold was implanted in each group. Samples were collected 1, 4, and 8 weeks after surgery to assess new bone formation and immune regulation.
[0078] Immune regulation effect:
[0079] H&E staining revealed a large number of inflammatory cells surrounding the scaffolds in all experimental groups, including the scaffold alone (control group) and the mesenchymal stem cell exosome (MSC-Exos) group. This suggests that neither the scaffold alone nor the scaffold combined with MSC-Exos effectively alleviates early inflammation. However, the MSC-Exos + miRNA group showed a significantly lower density of inflammatory cell infiltration compared to the other groups.
[0080] Osteogenesis effect analysis:
[0081] Eight weeks after surgery, H&E staining revealed that new bone formation was still minimal in the sham group, while the control, MSC-Exos, and MSC-Exos + miRNA-26a-5p groups displayed extensive bone ingrowth. The MSC-Exos + miRNA-26a-5p group had the highest proportion of mature bone tissue, highlighting its superior ability to promote new bone formation compared to the other groups.
[0082] Example 2: Construction of MSC-Exos hydrogel scaffold loaded with miRNA-30a-5p inhibitor on ATP (3%) / GelMA (8%) scaffold and study of its biological function
[0083] 1. Construction of MSC-Exos Hydrogel Scaffolds Loaded with miRNA-30a-5p Inhibitor
[0084] 3 wt% nano-attapulgite (ATP) powder was mixed with 8 wt% methacryloylated gelatin (GelMA) solution. 0.2 wt% LAP photoinitiator and 0.1 wt% TEA crosslinking agent were added to the mixture, which was then magnetically stirred at room temperature for 5 minutes. The resulting aqueous phase was then mixed with a 30 vol% dodecane / octane (1:1 mass ratio) oil phase in a 30:70 volume ratio. The mixture was stirred at 1000 rpm for 3 minutes, followed by ultrasonic treatment (150 W) for 5 minutes to produce a uniform and stable Pickering emulsion.
[0085] At a nozzle temperature of 27°C, an extrusion pressure of 0.18 MPa, and a printing speed of 2 mm / s, a Pickering emulsion was used to print porous cylindrical scaffolds with a diameter of 6 mm and a height of 1 mm. After printing, the scaffolds were cross-linked under 365 nm UV light for 10 minutes, resulting in a structurally stable ATP / GelMA scaffold. The scaffolds were then immersed in a PBS solution containing 0.5 μg / mL MSC-Exos and 300 nM miRNA-30a-5p inhibitor and incubated at 30°C for 12 hours. After removal and gentle washing, the miRNA-30a-5p-loaded MSC-Exos hydrogel scaffolds were obtained.
[0086] 2. Extraction and Characterization of MSC-Exos
[0087] Exosomes were extracted from mouse bone marrow mesenchymal stem cell (mBMSC) culture medium using the same method as in Example 1. After the cells reached 80% confluency, the medium was replaced with exosomal-free fetal bovine serum and cultured for another 48 hours. The supernatant was collected and exosomes were isolated by centrifugation at 300 × g, 2000 × g, 10,000 × g, and 100,000 × g, respectively.
[0088] Exosome Characterization:
[0089] NTA results showed that the particle size distribution was between 100–130 nm and the concentration was approximately 1.8 × 10 9 / mL;
[0090] TEM observation showed that the vesicle structure was intact and the morphology was a typical spherical vesicle;
[0091] Western blot results showed that CD63 and TSG101 were positively expressed, indicating that the extracted exosomes possessed typical markers.
[0092] 3. Characterization of miRNA-loaded Exosomes
[0093] Using Cy3 fluorescently labeled miRNA-30a-5p inhibitor, it was efficiently encapsulated into MSC-Exos by electroporation. Observation under a confocal microscope revealed that the Cy3 fluorescent signal highly overlapped with the CD63 marker protein, indicating that the miRNA was successfully localized inside the exosomes. Flow cytometry quantitative results showed that the exosomal miRNA loading efficiency was approximately 89%, the loading was stable, and no obvious aggregation or structural damage was observed. Figure 3 As shown in C and D, the particle size of exosomes loaded with miRNA-30a-5p inhibitors is concentrated in 110–140 nm, and the concentration is about 2.0×10 7 / mL, TEM showed typical vesicle structure.
[0094] 4. Scaffold structure and exosome release performance
[0095] SEM analysis:
[0096] like Figure 4 As shown in A, after drying, the scaffold was metallized. Scanning electron microscopy showed that the scaffold had a rich three-dimensional porous structure with pore sizes mainly concentrated between 300–400 μm. The internal connectivity was good, which was suitable for cell adhesion and exosome distribution. Figure 4 C shows that the average compressive strength test result of the bracket is 2200kPa.
[0097] Exos load situation:
[0098] like Figure 4 As shown in Figure B, the distribution of Exos inside the scaffold was observed under Cy3 fluorescence labeling. The red fluorescence was evenly distributed on the surface and inside of the scaffold, indicating that the exosomes were effectively adsorbed and embedded in the gel matrix.
[0099] Exos release pattern:
[0100] The loaded scaffolds were placed in PBS and incubated at 37°C. Supernatants were collected at predetermined time points and exosome release was measured using the BCA protein quantification assay. Results showed that the exosome release rate was slow during the first two days, then accelerated and remained stable, reaching a cumulative release of approximately 78% by day 14.
[0101] miRNA release pattern:
[0102] A Cy3 probe complementary to the antisense sequence of miRNA-30a-5p was designed and bound to the exosome supernatant for fluorescence detection. The results showed that miRNA release from the scaffold lasted for more than 10 days and the release process was smooth, with no significant burst release observed.
[0103] 5. Animal experiments to evaluate the effects of immune regulation and bone repair
[0104] A skull defect model was established in SD rats with a defect diameter of 6 mm on each side. The scaffold materials of this group were implanted. There were 12 rats in each group. Samples were collected and analyzed 1, 4, and 8 weeks after surgery.
[0105] Immune regulation effect:
[0106] One week after surgery, H&E staining results showed that a large number of inflammatory cells were still infiltrated around the stents in the simple stent group and the MSC-Exos group, while the number of inflammatory cells in the MSC-Exos+miRNA-30a-5p inhibitor group was significantly reduced, and the local inflammatory response was significantly alleviated.
[0107] Osteogenesis effect analysis:
[0108] Four weeks after surgery, H&E staining showed that the area of newly formed bone in the defect region of the miRNA-30a-5p inhibitor group was significantly greater than that of the blank scaffold and MSC-Exos groups. Furthermore, the trabeculae were neatly arranged, and the bone tissue structure was closer to that of natural bone. This result further confirms that the miRNA-30a-5p inhibitor-loaded MSC-Exos hydrogel scaffold has significant advantages in immune regulation and promoting bone regeneration.
[0109] Example 3: Construction and biological function study of MSC-Exos hydrogel scaffolds loaded with miRNA-26a-5p and miRNA-30a-5p inhibitors on ATP (1.5%) / GelMA (12%) scaffolds
[0110] 1. Construction of MSC-Exos hydrogel scaffolds loaded with miRNA-26a-5p and miRNA-30a-5p
[0111] A 1.5 wt% nano-attapulgite (ATP) powder was mixed with a 12 wt% methacryloylated gelatin (GelMA) solution. 0.1 wt% LAP photoinitiator and 0.1 wt% TEA crosslinking agent were added to the mixture, which was then magnetically stirred at room temperature for 5 minutes. The resulting aqueous phase was then mixed with a 30 vol% dodecane / octane (1:1 mass ratio) oil phase in a 30:70 volume ratio. The mixture was stirred at 1000 rpm for 3 minutes, followed by ultrasonic treatment (150 W) for 5 minutes to produce a uniform and stable Pickering emulsion.
[0112] At a nozzle temperature of 30°C, an extrusion pressure of 0.25 MPa, and a printing speed of 4 mm / s, a Pickering emulsion was used to print porous cylindrical scaffolds with a diameter of 6 mm and a height of 1 mm. After printing, the scaffolds were cross-linked under 365 nm UV light for 15 minutes to obtain a structurally stable ATP / GelMA scaffold. The scaffolds were then immersed in a PBS solution containing 1.0 μg / mL MSC-Exos and 400 nM miRNA-30a-5p inhibitor and incubated at 37°C for 15 hours. After removal and gentle washing, the dual-miRNA-loaded MSC-Exos hydrogel scaffolds were obtained.
[0113] 2. Extraction and Characterization of MSC-Exos
[0114] Mouse BMSCs were cultured for 48 hours without exosomes, and the supernatant was collected. The debris was removed by centrifugation at 300×g, 2000×g, 10,000×g, and 100,000×g to obtain the exosome precipitate.
[0115] NTA analysis: particle size distribution is 100–140 nm, and the concentration is about 2×10 9 / mL;
[0116] TEM showed typical round vesicles;
[0117] Western blot detection showed that the expression of exosome marker proteins CD63 and TSG101 was positive, indicating that the exosomes were successfully extracted.
[0118] 3. Characterization of miRNA-loaded Exosomes
[0119] miRNA-26a-5p and miRNA-30a-5p inhibitors were labeled with FITC and Cy3, respectively, and loaded into Exos via electroporation. Laser confocal microscopy revealed a high degree of overlap between the dual fluorescent signals and the CD63 marker, indicating successful dual-miRNA loading. Flow cytometry analysis demonstrated a loading efficiency exceeding 90% for both miRNAs, without compromising structural integrity.
[0120] 4. Scaffold structure and exosome release performance
[0121] SEM analysis:
[0122] Observation of the dried scaffolds after gold spraying revealed a continuous, regular, three-dimensional porous structure on both the surface and interior, with pore sizes ranging from 400–450 μm, supporting cell adhesion and nutrient exchange. The average compressive strength tested was 2500 kPa.
[0123] Exos load distribution:
[0124] FITC / Cy3 dual-channel excitation confocal microscopy was used for observation. The dual-channel signal distribution was consistent, and the exosomes were evenly distributed in the scaffold, without obvious accumulation or empty areas.
[0125] Exos release pattern:
[0126] The scaffolds were immersed in PBS and cultured at 37°C. The supernatants were collected at different time points and the protein release was detected by BCA method. Figure 5 As shown in A and B, exosomes were released continuously and stably, with the cumulative release reaching approximately 82% over 7 days.
[0127] miRNA release pattern:
[0128] Fluorescent probes corresponding to miRNA-26a-5p and miRNA-30a-5p inhibitors were used, combined with molecular hybridization technology to track the release. The results showed that the release process of the two miRNAs was smooth, lasting more than 12 days, and no sudden release was observed.
[0129] 5. Animal experiments to evaluate the effects of immune regulation and bone repair
[0130] The above-mentioned scaffolds were implanted into a 6mm bilateral skull defect model in SD rats. The experimental group was the MSC-Exos+miRNA-26a-5p+miRNA-30a-5p inhibitor combination group. Samples were collected and analyzed at 1, 4, and 8 weeks after surgery.
[0131] Immune regulation effect:
[0132] like Figure 6 As shown by the H&E staining results, the MSC-Exos+miRNA-26a-5p+miRNA-30a-5p inhibitor combined group (MSC-Exos+miRNA) significantly reduced inflammatory cell infiltration 1 week after surgery, which was better than the single miRNA group.
[0133] Osteogenesis effect analysis:
[0134] Likewise, if Figure 7 As shown in the MSC-Exos+miRNA-26a-5p+miRNA-30a-5p inhibitor complex group (MSC-Exos+miRNA), the bone defect area was well filled with mature bone tissue, bone bridges were fully formed, and bone repair was most significant.
[0135] After the simultaneous release of dual miRNAs, the polarization of macrophages M1→M2 is promoted far beyond the linear superposition effect, and the M2 proportion is increased from ~45–50% to more than ~70%, which is a non-obvious synergy that cannot be foreseen by existing technologies.
[0136] The porosity and mechanical strength of the scaffold were maintained without loss when Exos and dual miRNAs were loaded simultaneously at high loading rates, which also exceeded conventional expectations.
[0137] Comparative Example 1: Construction and biological function study of ATP (2.5%) / GelMA (9%) scaffold loaded with MSC-Exos hydrogel scaffold
[0138] 1. Construction of MSC-Exos-loaded Hydrogel Scaffolds
[0139] 2.5% nano-attapulgite (ATP) was mixed with 9% methacryloylated gelatin (GelMA) solution, and a uniform precursor solution was prepared using the Pickering emulsion method. The solution was loaded onto a bio-3D printing platform, with the nozzle temperature set at 25°C, the extrusion pressure set at 0.2 MPa, and the printing speed set at 3 mm / s. A cylindrical scaffold with a diameter of 6 mm and a height of 1 mm was printed. After printing, it was cross-linked by 405 nm UV light for 10 minutes to form a stable and degradable structure. The scaffold was immersed in PBS buffer containing 1 μg / mL MSC-Exos (unloaded with miRNA) and incubated at 37°C for 12 hours to uniformly load the exosomes onto the scaffold surface and inside the pores.
[0140] 2.5 wt% nano-attapulgite (ATP) powder was mixed with 9 wt% methacryloylated gelatin (GelMA) solution. 0.3 wt% LAP photoinitiator and 0.2 wt% TEA crosslinker were added to the mixture, which was then magnetically stirred at room temperature for 5 minutes. The resulting aqueous phase was then mixed with a 30 vol% dodecane / octane (1:1 mass ratio) oil phase in a 30:70 volume ratio. The mixture was stirred at 1000 rpm for 3 minutes, followed by ultrasonic treatment (150 W) for 5 minutes to produce a uniform and stable Pickering emulsion.
[0141] At a nozzle temperature of 25°C, an extrusion pressure of 0.3 MPa, and a printing speed of 2.5 mm / s, a Pickering emulsion was printed into a porous cylindrical scaffold with a diameter of 6 mm and a height of 1 mm. After printing, the scaffold was cross-linked under 405 nm UV light for 5 minutes to obtain a structurally stable ATP / GelMA scaffold. The scaffold was then immersed in a PBS solution containing 2.0 μg / mL MSC-Exos (unloaded with miRNA) and incubated at 37°C for 12 hours. The scaffold was removed and gently rinsed to obtain the MSC-Exos-loaded hydrogel scaffold.
[0142] 2. Extraction and Characterization of MSC-Exos
[0143] Exosomes were extracted from the culture supernatant of mouse bone marrow mesenchymal stem cells (mBMSCs) by ultracentrifugation.
[0144] Exosome characterization results:
[0145] NTA analysis showed that the particle size distribution was between 100–140 nm, and the concentration was approximately 1.8×10 9 / mL;
[0146] TEM observation showed that the vesicles were intact in morphology and presented a typical vesicle structure;
[0147] Western blot detection showed positive expression of CD63 and TSG101, indicating that exosomes were successfully extracted.
[0148] 3. Scaffold structure and exosome release performance
[0149] SEM observations revealed a porous structure on the dried scaffold surface, with pore sizes ranging from 370–440 μm and good connectivity. The average compressive strength test result was 2100 kPa.
[0150] Exos loading distribution: FITC-labeled MSC-Exos were evenly distributed in the scaffold, and the fluorescence imaging signal was continuous.
[0151] Exosomal release patterns: The scaffolds were placed in PBS and incubated at 37°C. The amount of exosome release was measured by BCA protein assay. The results showed that the exosomes were released slowly, with a cumulative release of approximately 78% on day 14.
[0152] 4. Animal Experiments to Evaluate Immune Regulation and Bone Repair
[0153] A skull defect model was established in SD rats, and the scaffolds were implanted. Samples were collected and analyzed 1, 4, and 8 weeks after surgery.
[0154] Immune regulation effect:
[0155] H&E staining showed moderate inflammatory cell infiltration around the stent one week after surgery. Flow cytometry analysis showed an increase in the proportion of CD206+ macrophages compared with the blank stent group, but significantly lower than that in the miRNA-loaded group.
[0156] Osteogenesis effect analysis:
[0157] Micro-CT scans at 8 weeks post-surgery showed new bone formation, but bone volume and density were lower than those in the miRNA-loaded group. H&E and Masson staining revealed limited new bone formation, loose trabecular connections, and fibrous tissue still present in the defect area.
[0158] Comparative Example 2: Construction and biological function study of ATP (2.0%) / GelMA (10%) blank hydrogel scaffold 1. Construction of blank hydrogel scaffold
[0159] 2.0 wt% nano-attapulgite (ATP) powder was mixed with 10 wt% methacryloylated gelatin (GelMA) solution. 0.1 wt% LAP photoinitiator and 0.1 wt% TEA crosslinking agent were added to the mixture, and magnetic stirring was performed at room temperature for 5 minutes. The resulting aqueous phase was mixed with a 30 vol% dodecane / octane (1:1 mass ratio) oil phase in a 30:70 volume ratio. The mixture was stirred at 1000 rpm for 3 minutes, followed by ultrasonic treatment (150 W) for 5 minutes to prepare a uniform and stable Pickering emulsion.
[0160] At a nozzle temperature of 20°C, an extrusion pressure of 0.2 MPa, and a printing speed of 4 mm / s, a Pickering emulsion was used to print a porous cylindrical scaffold with a diameter of 6 mm and a height of 1 mm. After printing, the scaffold was cross-linked under 405 nm UV light for 15 minutes, resulting in a structurally stable ATP / GelMA scaffold. This scaffold was not loaded with any exosomes or miRNA and served as a control group for evaluating the material's performance.
[0161] 2. Scaffold Structure Characterization
[0162] Scanning electron microscopy (SEM) observations revealed a well-connected porous network structure within the blank hydrogel scaffold, with pore sizes primarily ranging from 360–420 μm. This structure demonstrated a moderate cell-supporting capacity but lacked bioactive factors. The average compressive strength test result was 1700 kPa.
[0163] 3. Exosome loading and release performance
[0164] Since the blank scaffold was not loaded with MSC-Exos, there was no exosome release process and it was only used for comparison.
[0165] 4. Animal Experiments to Evaluate Immune Regulation and Bone Repair
[0166] A blank scaffold was implanted in the SD rat skull defect model, and samples were collected for analysis 1, 4, and 8 weeks after surgery.
[0167] Immune regulation effect:
[0168] One week after surgery, H&E staining revealed a large number of inflammatory cells infiltrating around the defect in the blank stent group, with the lowest proportion of CD206+ macrophages as detected by immunofluorescence. ELISA assays indicated elevated levels of IL-1β and TNF-α, while decreased levels of TGF-β and IL-10, indicating that inflammation was not effectively suppressed.
[0169] Osteogenesis effect analysis:
[0170] Micro-CT imaging at 8 weeks postoperatively showed minimal new bone formation, the lowest BV / TV ratio, and the lowest BMD. H&E and Masson staining revealed sparse new bone formation, indicating incomplete defect repair, with fibrous connective tissue still predominating.
[0171] Comparative Example 3: Construction and biological function study of ATP (2.0%) / GelMA (10%) blank hydrogel scaffolds directly loaded with miRNA-26a-5p and miRNA-30a-5p inhibitors
[0172] 1. Construction of blank hydrogel scaffolds directly loaded with miRNA
[0173] 2.0 wt% nano-attapulgite (ATP) powder was mixed with 10 wt% methacrylated gelatin (GelMA) solution. 0.3 wt% LAP photoinitiator and 0.2 wt% TEA co-crosslinker were added to the mixture, and magnetic stirring was performed at room temperature for 5 minutes. The resulting aqueous phase was mixed with a 30 vol% dodecane / octane (1:1 mass ratio) oil phase in a 30:70 volume ratio. The mixture was stirred at 1000 rpm for 3 minutes, followed by ultrasonic treatment (150 W) for 5 minutes to prepare a uniform and stable Pickering emulsion.
[0174] A Pickering emulsion was used to print porous cylindrical scaffolds with a diameter of 6 mm and a height of 1 mm at a nozzle temperature of 25°C, an extrusion pressure of 0.3 MPa, and a printing speed of 5 mm / s. After printing, the scaffolds were cross-linked under 365 nm UV light for 15 minutes, resulting in a structurally stable ATP / GelMA scaffold. The scaffolds were then immersed in 250 μL of PBS containing 300 nM each of miRNA-26a-5p and miRNA-30a-5p inhibitors and incubated at 37°C for 12 hours to allow the miRNA molecules to be physically adsorbed into the hydrogel scaffolds.
[0175] 2. Characterization of miRNA Loading
[0176] FITC and Cy3 were used to label miRNA-26a-5p and miRNA-30a-5p inhibitors, respectively. After incubation, the fluorescence imaging results of the scaffold showed that the dual fluorescence signals were evenly distributed, indicating that miRNA could be effectively adsorbed by the scaffold surface and pore structure.
[0177] Quantitative analysis of fluorescence intensity showed that the initial loading efficiency was high, but slightly lower than that of the MSC-Exos loaded scaffold. It was speculated that the direct adsorption method lacked a protective barrier, resulting in partial miRNA degradation.
[0178] 3. Scaffold structure and miRNA release performance
[0179] SEM observations revealed a porous three-dimensional network structure within the scaffold, with pore sizes ranging from 400–420 μm, similar to that of a blank scaffold. The average compressive strength test result was 2000 kPa.
[0180] miRNA release behavior:
[0181] The scaffolds were immersed in PBS and incubated at 37°C. Supernatants were collected at various time points and miRNA release was measured using molecular hybridization. Results showed a rapid increase in miRNA release within the first 48 hours, with a significant burst of release, followed by a gradual release. After day 10, miRNA release approached saturation, indicating poor stability.
[0182] 4. Animal Experiments to Evaluate Immune Regulation and Bone Repair
[0183] Blank scaffolds directly loaded with miRNAs were implanted into the SD rat skull defect model, and samples were collected for analysis at 1, 4, and 8 weeks after surgery.
[0184] Immune regulation effect:
[0185] One week after surgery, HE staining revealed a decrease in the number of inflammatory cells surrounding the stent, significantly lower than in the blank stent group but lower than in the MSC-Exos-miRNA-loaded group. Flow cytometry assays revealed an increase in the proportion of CD206+ macrophages, while ELISA assays revealed decreased IL-1β and TNF-α expression and a slight increase in SOCS3 levels. However, the overall immune regulatory effect was inferior to that observed in the MSC-Exos-delivered group.
[0186] Osteogenesis effect analysis:
[0187] Micro-CT three-dimensional reconstruction revealed a moderate amount of new bone formation in the defect area of this group. The BV / TV ratio was significantly higher than that of the blank scaffold group, but lower than that of the MSC-Exos-miRNA-delivered group. H&E and Masson staining revealed an increase in new bone mass, but sparse trabeculae and poor connectivity. qPCR analysis revealed an increase in the expression of osteogenesis-related genes, Runx2 and OCN, but the magnitude was less than that observed with the MSC-Exos-miRNA-delivered scaffold.
[0188] Comparative Example 4: ATP (2%) / GelMA (10%) blank hydrogel scaffold directly mixed with MSC-Exos, miRNA-26a-5p inhibitor and miRNA-30a-5p inhibitor
[0189] 1. Construction of a hydrogel scaffold for direct mixing of exosomes and miRNA
[0190] 2 wt% nano-attapulgite (ATP) powder was mixed with 10 wt% methacrylated gelatin (GelMA) solution, and 0.3 wt% LAP photoinitiator and 0.1 wt% TEA co-crosslinker were added. The mixture was magnetically stirred at room temperature for 5 minutes. The resulting aqueous phase was then mixed with a 30 vol% dodecane / octane (1:1 mass ratio) oil phase at a volume ratio of 30:70 at 1000 rpm for 3 minutes. The mixture was then ultrasonicated (150 W) for 5 minutes to obtain a uniform and stable Pickering emulsion.
[0191] Under the conditions of nozzle temperature of 25°C, extrusion pressure of 0.2MPa and printing speed of 3mm / s, a porous cylindrical scaffold with a diameter of 6mm and a height of 1mm was printed using a bioprinter; after printing, it was irradiated under 405nm ultraviolet light for 10 minutes for cross-linking to obtain a structurally stable ATP / GelMA hydrogel scaffold.
[0192] After the scaffold was prepared, it was directly immersed in a PBS solution containing 1 μg / mL MSC-Exos, 200 nM miRNA-26a-5p, and 300 nM miRNA-30a-5p inhibitors and incubated at 37°C for 12 hours. Without any engineering coating or electroporation, MSC-Exos and the two miRNAs were loaded onto the scaffold matrix by physical adsorption.
[0193] 2. Characterization of miRNA Loading
[0194] FITC and Cy3 were used to label miRNA-26a-5p and miRNA-30a-5p inhibitors, respectively. After incubation, the fluorescence imaging results of the scaffold showed that the dual fluorescence signals were evenly distributed, indicating that miRNA could be effectively adsorbed by the scaffold surface and pore structure.
[0195] Quantitative analysis of fluorescence intensity showed that the initial loading efficiency was lower than that of the engineered exosome encapsulation treatment, presumably because the direct adsorption method lacked a protective barrier, leading to partial miRNA degradation.
[0196] 3. Scaffold structure and exosome release performance
[0197] SEM observations revealed a well-connected porous network structure within the hydrogel scaffold, with pore sizes primarily concentrated between 320 and 350 μm. This structure demonstrated a moderate cell-supporting capacity but lacked bioactive factors. The average compressive strength test result was 2200 kPa.
[0198] Exos loading distribution: FITC-labeled MSC-Exos were evenly distributed in the scaffold, and the fluorescence imaging signal was continuous.
[0199] miRNA release behavior:
[0200] The scaffolds were immersed in PBS and incubated at 37°C. Supernatants were collected at various time points and miRNA release was measured using molecular hybridization. The results showed that miRNA release increased rapidly in the first 12 hours, with a significant burst of release, followed by a gradual release. After the third day, miRNA release approached saturation, indicating poor stability.
[0201] 4. Animal Experiments to Evaluate Immune Regulation and Bone Repair
[0202] A blank scaffold was implanted in the SD rat skull defect model, and samples were collected for analysis 1, 4, and 8 weeks after surgery.
[0203] Immune regulation effect:
[0204] One week after surgery, H&E staining revealed a large number of inflammatory cells infiltrating around the defect in the blank stent group, with the lowest proportion of CD206+ macrophages as detected by immunofluorescence. ELISA assays indicated elevated levels of IL-1β and TNF-α, while decreased levels of TGF-β and IL-10, indicating that inflammation was not effectively suppressed.
[0205] Osteogenesis effect analysis:
[0206] Micro-CT imaging at 8 weeks postoperatively showed minimal new bone formation, the lowest BV / TV ratio, and the lowest BMD. H&E and Masson staining revealed sparse new bone formation, indicating incomplete defect repair, with fibrous connective tissue still predominating.
[0207] The above detailed description of the present invention is intended to enable persons familiar with the art to understand the contents of the present invention and implement them. It does not limit the scope of protection of the present invention. The present invention is not limited to the above embodiments. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a functionalized bone repair hydrogel scaffold, characterized in that: The following steps are involved: Nano-attapulgite is mixed with methacrylated gelatin to form a printable emulsion system, the printable emulsion system is three-dimensionally printed and ultraviolet cross-linked to form a porous three-dimensional scaffold, and the porous three-dimensional scaffold is incubated in a PBS solution containing mesenchymal stem cell exosomes and miRNA-26a-5p and / or miRNA-30a-5p, so that the mesenchymal stem cell exosomes and miRNA-26a-5p and / or miRNA-30a-5p are co-loaded on the porous three-dimensional scaffold.
2. The method for preparing a functionalized bone repair hydrogel scaffold according to claim 1, characterized in that: The steps of mixing to form a printable emulsion system specifically include: Nano-attapulgite powder is mixed with a methacrylated gelatin solution, and a photoinitiator, lithium phenol-2,4,6-trimethylphenylphosphonate, and a cross-linking agent, triethanolamine, are added to the resulting mixture, and the mixture is magnetically stirred to obtain a uniform aqueous phase. The aqueous phase is magnetically stirred and uniformly mixed with an oil phase mixed with dodecane and octane, and then ultrasonically treated to obtain a stable, uniform, and printable Pickering emulsion, wherein the mass ratio of nano-attapulgite powder to methacrylated gelatin, lithium phenol-2,4,6-trimethylphenylphosphonate, and triethanolamine is (1.0-4.0):(5.0-15.0):(0.05-0.3):(0.05-0.3), and the volume ratio of the aqueous phase to the oil phase is 1:1-1:
6.
3. The method for preparing a functionalized bone repair hydrogel scaffold according to claim 1, characterized in that: The printing cross-linking steps specifically include: The nozzle temperature is set to 20-30° C., the extrusion pressure is set to 0.1-0.3 MPa, and the printing speed is set to 1-5 mm / s. Three-dimensional printing is performed according to the printing parameters. After printing is completed, cross-linking is performed under 365-405 nm ultraviolet light for 5-15 minutes.
4. The method for preparing a functionalized bone repair hydrogel scaffold according to claim 1, wherein: The incubation steps specifically include: The porous three-dimensional scaffold was immersed in a PBS solution containing 0.5–2 μg / mL MSC-Exos, 200–500 nM miRNA-26a-5p, and 200–500 nM miRNA-30a-5p, and incubated at 25–45°C for 4–24 h to complete the loading.
5. The method for preparing a functionalized bone repair hydrogel scaffold according to claim 1, characterized in that: The miRNA is miRNA-26a-5p, miRNA-30a-5p or a combination thereof. When a single miRNA is loaded, the molar ratio of mesenchymal stem cell exosomes to the loaded miRNA is 1:50 to 1:500; when a combination of miRNAs is loaded, the molar ratio of mesenchymal stem cell exosomes to the loaded miRNA-26a-5p is 1:50 to 1:500; the molar ratio of mesenchymal stem cell exosomes to the loaded miRNA-30a-5p is 1:50 to 1:500; and the molar ratio of miRNA-26a-5p to miRNA-30a-5p is 1:0.5 to 1:
2.
6. The method for preparing a functionalized bone repair hydrogel scaffold according to claim 1, characterized in that: The mesenchymal stem cell exosomes are extracted by ultracentrifugation, and have an average particle size of 100-140 nm.
7. The method for preparing a functionalized bone repair hydrogel scaffold according to claim 1, characterized in that: The porous three-dimensional scaffold has a pore size of 60-150 μm and a compressive strength of 1000-3000 kPa.
8. A functionalized bone repair hydrogel scaffold, characterized in that: The functionalized bone repair hydrogel scaffold is prepared by the method according to any one of claims 1 to 9, and has a three-dimensional porous structure and a surface stably loaded with components of mesenchymal stem cell exosomes and the miRNA-26a-5p and / or miRNA-30a-5p they carry.
9. Use of the bone repair hydrogel scaffold according to claim 8 in repairing bone defects.
10. Use of the bone repair hydrogel scaffold according to claim 8 in a tissue engineering material for regulating the SOCS3 signaling pathway and reducing the expression of inflammatory factors.
Citation Information
Cited By
ROS response 3D printing shape memory material loaded with camel milk source exosome as well as preparation method and application of ROS response 3D printing shape memory material
CN121221856A